2010
DOI: 10.1016/j.vibspec.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the surface functionalities and adsorption evolution of water molecules on silica gel surface: A study by second derivative near infrared spectroscopy

Abstract: Surface functionalities and adsorption evolution of water molecules on silica gel samples were studied by second derivative Near Infrared Spectroscopy. Four different silica gel samples with varying surface area were used in this experiment. Each of the dry samples was allowed to equilibrate with surrounding air and the near infrared spectra were accumulated at different time intervals using reflectance technique. The evolved spectra were analysed by using second derivative technique to study the adsorption ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 27 publications
3
95
0
Order By: Relevance
“…One can clearly observe that a peak arise in the region 5300-5000 cm -1 purely from the water molecules adsorbed on the surface. A second derivative operation reveals that there are two different bands in this broad peak and the band at 5270 cm -1 is due to the water molecules adsorbed onto hydrogen bonded silanol groups and the band at 5314 cm -1 is due the water molecules adsorbed onto the free silanol groups on the surface [16]. Even though, the methodology used in this study is not direct, it gives clear picture of the nature of functionalities on silica gel surface.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…One can clearly observe that a peak arise in the region 5300-5000 cm -1 purely from the water molecules adsorbed on the surface. A second derivative operation reveals that there are two different bands in this broad peak and the band at 5270 cm -1 is due to the water molecules adsorbed onto hydrogen bonded silanol groups and the band at 5314 cm -1 is due the water molecules adsorbed onto the free silanol groups on the surface [16]. Even though, the methodology used in this study is not direct, it gives clear picture of the nature of functionalities on silica gel surface.…”
Section: Introductionmentioning
confidence: 93%
“…Christy [16] has studied several silica gel samples and their water adsorption evolutions using garvimetry and near infrared transflectance spectroscopy with the help of second derivative techniques and showed that the hydrogen bonded silanol groups adsorb water readily compared to free silanol groups. Furthermore, an equal proportion of free and hydrogen bonded silanol groups are needed for effective water adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Near infrared spectroscopy was chosen as the preferred analytical technique. Christy [5][6][7] has used near infrared spectroscopy in combination with second and fourth-derivative techniques and gravimetry to show the water adsorption properties of silicagel and silicagel related materials [5][6][7]. A similar approach was used in following the adsorption behavior of water on cellulose and CNCs surface.…”
Section: Introductionmentioning
confidence: 99%
“…Since this absorption is purely from water molecules adsorbed on to the OH groups on the surface of the adsorbent, the band structure of the above peak revealed by the second and fourth derivative techniques can be directly connected to the different types of surface OH groups. With the help of near infrared reflection spectroscopy combined with second and derivative techniques, Christy has published a series of articles [7][8][9][10] regarding the nature of OH groups and their affinity to water molecules in different substances. Christy was able to distinguish the near infrared absorption bands arising from the water molecules hydrogen bonded silanol groups and water molecules hydrogen bonded to vicinal silanol groups [7].…”
Section: Introductionmentioning
confidence: 99%
“…With the help of near infrared reflection spectroscopy combined with second and derivative techniques, Christy has published a series of articles [7][8][9][10] regarding the nature of OH groups and their affinity to water molecules in different substances. Christy was able to distinguish the near infrared absorption bands arising from the water molecules hydrogen bonded silanol groups and water molecules hydrogen bonded to vicinal silanol groups [7]. Furthermore, the near infrared absorption bands arising from the water molecules hydrogen bonded to different OH groups in the carbohydrate polymers were identified [10].…”
Section: Introductionmentioning
confidence: 99%